2009
DOI: 10.1002/ange.200805661
|View full text |Cite
|
Sign up to set email alerts
|

Pd‐PEPPSI‐IPent: An Active, Sterically Demanding Cross‐Coupling Catalyst and Its Application in the Synthesis of Tetra‐Ortho‐Substituted Biaryls

Abstract: Variable Größe: Eine Reihe von Katalysatoren mit N‐heterocyclischen Carbenliganden (siehe Beispiel) wurde hergestellt und in der Suzuki‐Miyaura‐Reaktion getestet. Mit einem Isopentyl‐substituierten Katalysator wurden die sterisch befrachteten vierfach ortho‐substituierten Biarylprodukte aus wenig reaktiven Arylchloriden zwischen Raumtemperatur und 65 °C erhalten. Dass der Cyclopentyl‐substituierte Katalysator praktisch nicht aktiv war, zeigt die entscheidende Bedeutung eines „flexiblen Raumbedarfs“ bei diesen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
64
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 139 publications
(78 citation statements)
references
References 32 publications
(27 reference statements)
7
64
0
6
Order By: Relevance
“…[5] Consistent with this, we demonstrated that electron-rich aryl halides, once added to Pd, suppress the amination cycle by discouraging amine coordination to the metal and/or subsequent deprotonation of the aryl palladium amide complex. Further, we showed that the Pd-PEPPSI-IPent NHC catalyst (5; PEPPSI = pyridine, enhanced precatalyst, preparation, stabilization, and initiation; IPent = diisopentylphenylimidazolium; see Table 1) [6,7] was suitably electron poor at Pd to still be able to negotiate these steps, while the more electronrich (relatively) Pd-PEPPSI-IPr derivative (4; IPr = diisopropylphenylimidazolium) could not. [1] Not unlike the catalysts metal centre that must walk an electronic tightrope to allow electronically divergent steps to occur, so must the amine.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Consistent with this, we demonstrated that electron-rich aryl halides, once added to Pd, suppress the amination cycle by discouraging amine coordination to the metal and/or subsequent deprotonation of the aryl palladium amide complex. Further, we showed that the Pd-PEPPSI-IPent NHC catalyst (5; PEPPSI = pyridine, enhanced precatalyst, preparation, stabilization, and initiation; IPent = diisopentylphenylimidazolium; see Table 1) [6,7] was suitably electron poor at Pd to still be able to negotiate these steps, while the more electronrich (relatively) Pd-PEPPSI-IPr derivative (4; IPr = diisopropylphenylimidazolium) could not. [1] Not unlike the catalysts metal centre that must walk an electronic tightrope to allow electronically divergent steps to occur, so must the amine.…”
Section: Introductionmentioning
confidence: 99%
“…With the aid of spectroscopy and calculation, we have preliminary data to suggest that increasing the bulk around the coordination sphere of Pd leads to an increase in the positive charge on the metal. [8,9] Following this trend, we have further enhanced NHC bulk with the creation of Pd-PEPPSI-IPent (18, Figure 1) [10] and investigated this effect on amination reactions employing rate studies and computation; the results are detailed below.…”
mentioning
confidence: 98%
“…When the oxidative addition partner became more hindered the bromide now required 110 8C to complete (Table 1, entry 2) and the corresponding chloride now failed to couple at all (0 %), even under the most forcing conditions (Table 1, entry 4). Pd-PEPPSI-IPent has been demonstrated to be highly active in low-temperature Suzuki-Miyaura, [11,12] Negishi, [13] and Stille-Migita [14] couplings, thus we opted to examine its reactivity focusing only on hindered 2,6-dimethyl substrates. Initially, no reactivity at all was observed at 40 8C (Table 1, entry 5).…”
mentioning
confidence: 99%